Motor Vehicle Exhaust Emissions in Delhi (International Journal of Current Engineering and Technology, 2014)
Delhi is a rapidly expanding mega city. Population and vehicle use continue to expand, with vehicles being the principal source of severe air pollution. In the present study, we attempt to resolve the complications of Delhi's transport sector, exploring what kind of a future is likely to be and how it may be altered to ensure minimum environmental pollution. In the ultimate analysis, we were able to come out with a conceptual strategy, which if implemented in its entire suggested framework, has the potential of bringing down the current environmental pollution levels drastically and promises to be commercially viable too. In this paper some novel approaches to mitigate the Delhi’s vehicular pollution are discussed.
Keywords: Public Transport, Vehicle Emissions, Environmental Pollution.